Dietary supplementation with Bacillus subtilis KC1 alleviates the negative effects of Mycoplasma gallisepticum on growth performance and amino acid metabolism of broiler chickens - Chen, Xueping; Cui, Jiayao; Wang, Yuanyuan; Han, Keguang; Huo, Nairui; Wang, Jian (Frontiers in Veterinary Science, 2024)
The aim of this study was to explore whether and how Bacillus subtilis KC1 can enhance the growth performance of Mycoplasma gallisepticum (MG)-infected broilers. Broilers were randomly divided into 4 groups: the control group (basal diet), the MG group (basal diet + MG challenge), the KC group (basal diet + B. subtilis KC1 supplementation), the KC + MG group (basal diet + B. subtilis KC1 supplementation + MG challenge). The results showed that, compared to the control group, MG group exhibited significantly reduced body weight and average daily gain, and increased feed conversion ratio of broilers. However, compared to the MG group, the B. subtilis KC1 + MG group exhibited significantly improved above indicators of growth performance. In addition, compared to the MG group, B. subtilis KC1 + MG group exhibited increased superoxide dismutase levels and reduced levels of malondialdehyde, interleukin-1β, and tumor necrosis factor-α of broilers. Furthermore, metabolomics and transcriptomics analyses indicated that MG infection disrupted amino acid metabolism in broilers, whereas B. subtilis KC1 supplementation alleviated the abnormal amino acid metabolism caused by MG. These results suggested that B. subtilis KC1 may alleviate the poor growth performance caused by MG infection in broilers by improving amino acid metabolism.